Electrochemical kinetics of Li insertion in nanosized high performance V2O5 obtained via fluorine chemistry. (1st November 2017) - Huo, D.; Laïk, B.; Bonnet, P.; Guérin, K.; Baddour-Hadjean, R.; Pereira-Ramos, J-P.
Graphical abstract: Abstract: The kinetics of the electrochemical lithium insertion reaction in nanosized V2 O5 prepared from a fluorination synthesis in solution is investigated by AC impedance spectroscopy. The experimental data are obtained vs. x in nano-Lix V2 O5 over the wide composition range 0 ≤ x < 1.8 and vs. temperature. Kinetic parameters for Li electroinsertion in nanosized V2 O5 are achieved here for the first time. The charge transfer kinetics is little affected by Li content. A moderate evolution of the chemical diffusion coefficient is related to the peculiar single-phase behavior induced by the nanosize effect combined with shorter Li diffusion pathways. Comparison with experimental data obtained for microsized analogue vs. temperature reveals a much lower activation energy barrier (0.06 eV) for the lithium diffusion process in nanosized V2 O5 that explains the significant improvement in electrochemical performances and especially a better rate capability. This work illustrates how nanosizing promotes the kinetics of Li insertion reaction, in agreement with the new and specific structural response of nanosized vanadium pentoxide.